2019
DOI: 10.1002/ange.201904860
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HER2‐Positive Breast Cancer Growth by Blocking the HER2 Signaling Pathway with HER2‐Glycan‐Imprinted Nanoparticles

Abstract: Blocking the HER2 signaling pathway has been an effective strategy in the treatment of HER2-positive breast cancer.I tm ainly relies on the use of monoclonal antibodies and tyrosine-kinase inhibitors.H erein, we present an ew strategy,the nano molecularly imprinted polymer (nanoMIP). The nanoMIPs,imprinted using HER2 N-glycans,could bind almost all HER2 glycans and suppress the dimerization of HER2 with other HER family members,b locking the downstream signaling pathways,t herebyi nhibiting HER2 + breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…This idea follows the rationale reported for other drug targets, such as Her-2 (50-52). In addition, approaches aiming at inducing cell toxicity based on oncogene expression are already used in other tumor models, such as in Her2-positive breast, gastric and esophageal cancer, in which distinct strategies have been proposed to block Her2-induced tumor growth (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…This idea follows the rationale reported for other drug targets, such as Her-2 (50-52). In addition, approaches aiming at inducing cell toxicity based on oncogene expression are already used in other tumor models, such as in Her2-positive breast, gastric and esophageal cancer, in which distinct strategies have been proposed to block Her2-induced tumor growth (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…3 Her2, a member of the transmembrane epidermal growth factor receptor family, is found to be overexpressed in approximately 25–30% of human primary breast cancers, associated with aggressive tumor behavior, higher remote metastasis, and poor clinical outcomes. 4,5 Moreover, it is found that Her2-positive breast cancers are prone to resistance to chemotherapy or hormone therapy. 3,6 Therefore, we envisaged an early stage, precise, targeted therapies for Her2-positive breast cancer, while monitoring and evaluating the treatment process in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…Worth mentioning is the challenge of producing nanoMIP architectures suitable to translating MIP-mediated cell-recognition from the passive stage of binding to its defined target, to the active intervention in the cell biology process. To accomplish this important step,the integrated design of MIPs with multi-functions is expected, gathering in a single nanoMIP particle ability to activate or silence biochemical pathways[37,120]. The success in this area will result and in new paradigms for MIP applications both complementing existing therapeutic and diagnostic techniques and opening doors to in situ programmed nanomachines for precision medicine interventions and tissue regeneration.…”
mentioning
confidence: 99%